"Task-oriented" exercise improves hamstring strength and spastic reflexes in chronic stroke patients - Smith, G V; Silver, K H; Goldberg, A P; Macko, R F (Stroke (1970), 1999)
Despite the belief that after cerebral infarction only limited functional gains are possible beyond the subacute period, we tested the hypothesis that a 12-week program of "task-oriented" treadmill exercise would increase muscle strength and decrease spastic reflexes in chronic hemiparetic patients. Fourteen subjects, aged 66+/-3 (mean+/-SEM) years, with residual gait deviations due to remote stroke (>6 months), underwent repeated measures of reflexive and volitional (concentric and eccentric) torque with use of isokinetic dynamometry on the hamstring musculature bilaterally. Torque output was measured at 4 angular velocities (30(o), 60(o), 90(o), and 120(o)/s). After 3 months of 3 times/wk low-intensity aerobic exercise, there were significant main effects (2 legs [P<0.01]x2 times [P<0. 01]x4 angular velocities [P<0.05]) for concentric torque production. Torque/time production in the concentric mode also improved significantly in the paretic (50%, P<0.01) and nonparetic hamstrings (31%, P<0.01). Eccentric torque/time production increased by 21% (P<0.01) and 22% (P<0.01) in the paretic and nonparetic hamstrings, respectively. Passive (reflexive) torque/time generation in the paretic hamstrings decreased by 11% (P<0.027). Reflexive torque/time was unchanged in the nonparetic hamstrings (P=0.45). These findings provide evidence that progressive treadmill aerobic exercise training improves volitional torque and torque/time generation and reduces reflexive torque/time production in the hemiparetic limb. Strength changes associated with improved functional mobility in chronic hemiparetic stroke survivors after treadmill training will be reported in future articles.